The transformation of the image of God during the development of eating disorders and eventual therapy: a sociological study - Dariusz Tułowiecki (Warszawskie Studia Teologiczne)
The text aims to present the image of God – a Higher Power being discovered as part of eating disorder therapy and the changes in the informant within her life. The text is based on empirical material obtained through a case study of a person experiencing eating disorders, who started therapy in an OA group. Her eating disorders took the form of anorexia, addiction to dieting, and bulimia. While attending the group, the respondent goes through the 12 steps of OA, which assume acknowledging one’s powerlessness against eating disorders, discovering a Higher Power which can make one recover, committing one’s life to God – the Higher Power, and building a bond with God through prayer, regardless of the way God is perceived. The case study was conducted by means of a series of interviews with a young woman who declared herself to be a Catholic with a strong distance from the institution of church. She is a believer, occasionally practicing, with a high level of religious tolerance, anti-clerical, for whom God is a relational creature who comes to the rescue and gives acceptance – an idea of a perfect, unconditionally loving father.